Metode Penyusunan Kitab Mu'jam Al-wajiz min Ahadith Al-rasul Al-aziz - Salman Abdul Muthalib (Fakultas Ushuluddin dan Filsafat UIN Ar-raniry Banda Aceh, 2012)
Mu‘jam al-Wajiz Min Ahadith al-Rasul al-‘aziz is one of classic work in hadist, which is still written in manuscript. The manuscript is posed by Acehnese community. It is compellation of hadist which is structured alphabetically. Collected hadist is started by letter of alif, which is followed by ba’ and so on following Arabic alphabet order. This structure ease people in searching particular hadist. Moreover, the author mentioned mukharrij in every end of hadist, which is also important to initiate takhrij hadist.